BEBERAPA JENIS METABOLIT SEKUNDER YANG BERPOTENSI SEBAGAI ANTI KANKER : A MINI REVIEW - Rizkirullah, Muhammad Adhitya; Kartika, Rudi; Aswat, Raihan; Mahrus, Muhammad Haissul; Rahman, Fatur; Kurniawan, Andi; Azka, Andi Aulia Urrahman; Sanian, Sanian (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Cancer is one of the leading causes of death worldwide, including in Indonesia. This review explores the potential of various plants as sources of anticancer compounds through secondary metabolite analysis. Plants such as Rosa damascena, Wild Onion (Scorodocarpus borneensis Becc), and Acalypha Indica have been studied for anticancer activity using in vitro methods. The results showed that extracts from Rosa damascena had varying IC50 values ​​against various types of cancer cells, including 16.28 μg/mL in liver cancer cells (HepG-2) and 18.09 μg/mL in breast cancer cells (MCF-7). In addition, Wild Onion showed very strong anticancer activity with an IC50 value of 1.1061 μg/mL in L1210 leukemia cells. Secondary metabolites such as flavonoids, alkaloids, and tannins were identified as key components contributing to the anticancer effects. These findings highlight the importance of further research to develop more effective and safe plant-based cancer therapies. Keyword: Anticancer, Cancer, Secondary Metabolites, Plants